ANALISIS PENGARUH BIAYA OPERASIONAL DAN VOLUME PENJUALAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR PERALATAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Catur Kumala dewi 3, Alfitriana Eddy Soegiarto 2 (EKONOMIA, 2020)
This study aims to determine the increase in operational costs can reduce return on assets and increase sales volume can increase return on assets in household equipment sub-sector companies listed on the Indonesia Stock Exchange.       Methods empirically in used is quantitative methods and techniques of data collection is done in retrieving data from the literature (library research)  from the  www.idx.co.id , and after the sample selection by using purposive sampling acquired 4 companies that meet criteria used in the study. The independent variable used is operational costs and sales volume, and the dependent variable used is financial performance. The analytical tool used in this research is comparative comparative analysis.       The results of the study show that the increase in operational costs is not always accompanied by a decrease in return on assets, in the household equipment sub-sector companies registered at The Indonesia Stock Exchange for the 2014-2018 period and an increase in sales volume is not always accompanied by an increase in return on assets in the company's assets so that the return on assets did not experience an increase in the household appliances sub sector listed on the Indonesia Stock Exchange in the 2014-2018 period.